2015
DOI: 10.1007/s10753-015-0158-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth Differentiation Factor-15 Is a Novel Biomarker Predicting Acute Exacerbation of Chronic Obstructive Pulmonary Disease

Abstract: Exacerbations in chronic obstructive pulmonary disease (COPD) reduce quality of life and are associated with a more rapid deterioration of the disease. Growth differentiation factor-15 (GDF-15) is a novel candidate exacerbation biomarker. In this study, we aimed to assess GDF-15 as a biomarker of acute exacerbation of COPD (AE-COPD). Lung function parameters, arterial blood gas analysis, and circulating levels of GDF-15, C-reactive protein (CRP), and fibrinogen were assessed in 29 patients on admission to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
1
24
0
Order By: Relevance
“…Fourth, there is a lack of longitudinal follow-up for some of the patients, especially among patients with an apparently poor prognosis at inclusion and also with a high mortality, thus our findings in this patient category may be less robust (see supplementary material for details). Finally, although increased systemic levels of GDF15 are associated with both COPD [21] and lung injury [11], GDF15 is not lung specific, and we cannot tell whether the source of GDF15 is from lung tissue or other organ systems.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Fourth, there is a lack of longitudinal follow-up for some of the patients, especially among patients with an apparently poor prognosis at inclusion and also with a high mortality, thus our findings in this patient category may be less robust (see supplementary material for details). Finally, although increased systemic levels of GDF15 are associated with both COPD [21] and lung injury [11], GDF15 is not lung specific, and we cannot tell whether the source of GDF15 is from lung tissue or other organ systems.…”
Section: Discussionmentioning
confidence: 95%
“…As a cytokine associated with both inflammation and cachexia, along with increased mortality, GDF15 is of interest in patients with COPD, both as a diagnostic or prognostic biomarker and as a potential treatment target. A few smaller studies have examined GDF15 in COPD, indicating elevated plasma levels of GDF15 in patients with COPD [21,22], and an additional increase during COPD exacerbations [21,23,24]. Nevertheless, the role of GDF15 as a prognostic biomarker in COPD is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Until now, only circulating GDF-15 levels were reported to be increased in stable COPD and during acute exacerbations of COPD and identified to be an independent predictor of acute exacerbations. [17][18][19] Equivalently, GDF-15 is augmented in serum and lung tissue of patients with pulmonary arterial hypertension. 20,21 Lambrecht et al 22 showed that serum GDF-15 levels correlate with the extent of lung fibrosis in patients with systemic sclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…16 Recently, increased serum levels of GDF-15 have been shown in patients with COPD under stable conditions and during acute exacerbations. [17][18][19] In this study, we explored the potential role of GDF-15 in CS-induced inflammation and COPD. We first analyzed the expression of GDF-15 in the airways and lungs of patients with COPD, in CS-exposed cultures of primary human bronchial epithelial cell cultures (pHBECs) and in lungs of CS-exposed mice.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested to have an overall anti-inflammatory effect and is elevated in inflammatory scenarios associated with cancer, cardiovascular disease, insulin resistance and obesity 25 , as a compensatory mechanism 26 28 . GDF15 levels have been reported to correlate with CRP levels in certain inflammatory disorders 29 , 30 . In addition to its growing relevance as a marker of inflammation 26 and all-cause mortality 31 , GDF15 has been described in the literature to have neurotrophic 32 , 33 and anti-apoptotic properties 34 .…”
Section: Introductionmentioning
confidence: 99%